'Prudent habitat choice': a novel mechanism of size‐assortative mating. (6th May 2014) - Taborsky, B.; Guyer, L.; Demus, P.
Abstract Assortative mating, an ubiquitous form of nonrandom mating, strongly impacts Darwinian fitness and can drive biological diversification. Despite its ecological and evolutionary importance, the behavioural processes underlying assortative mating are often unknown, and in particular, mechanisms not involving mate choice have been largely ignored so far. Here, we propose that assortative mating can arise from 'prudent habitat choice', a general mechanism that acts under natural selection, and that it can occur despite a complete mixing of phenotypes. We show that in the cichlid Eretmodus cyanostictus size‐assortative mating ensues, because individuals of weaker competitive ability ignore high‐quality but strongly competed habitat patches. Previous studies showed that in E. cyanostictus, size‐based mate preferences are absent. By field and laboratory experiments, here we showed that (i) habitat quality and body size are correlated in this species; (ii) territories with more stone cover are preferred by both sexes in the absence of competition; and (iii) smaller fish prudently occupy vacant territories of worse quality than do larger fish. Prudent habitat choice is likely to be a widespread mechanism of assortative mating, as both preferences for and dominance‐based access to high‐quality habitats are generic phenomena in animals.